“Comprehensive Analysis Of Ddos Attack Mitigation Using Software-Defined Networking Strategies: Exploring Challenges And Key Factors” - Mr. Janak H. Maru; Dr. Ashish M. Kothari; Ms. Priyanka Dobariya (Educational Administration: Theory and Practice, 2024)
Distributed Denial of Service (DDoS) attacks continue to pose significant threats to network infrastructure and services. As the complexity and scale of these attacks grow, traditional methods of defense are becoming less effective. This research paper presents a comprehensive analysis of DDoS attack mitigation using Software-Defined Networking (SDN) strategies, shedding light on the challenges faced and the key factors that influence the effectiveness of SDN-based solutions.